Clinico-Epidemiological Profile of Patients with COVID-19 in a Tertiary Care Centre of Mid-Western Nepal - Karki, Shravya Singh; Basnet, Pragya S; Karki, Sauharda S; Lamichhane, Basant; Sharma, Damodar; Acharya, Birendra K; KC, Sunil; Seikh, Salman; Kunwar, Santosh; Rajbhandari, Nishtha; et al. (Nepalese Medical Journal, 2021)
Introduction: With little to no research done that sheds light on the COVID-19 pandemic in the Mid-Western region of Nepal, this study attempts to educate the general populace and concerned authorities on the impact of the pandemic in the region. Materials and Methods: Patients presenting at Rapti Academy of Health Sciences between 14 May 2020 to December 21, 2020, diagnosed with COVID-19 were included in the study. These patients were reviewed for age, sex, address, recent travel history, and presenting symptoms. Results: A total of 3895 COVID -19 positive individuals were included in the study. The mean age of the patients was 33.6 ± 13.8 years, a majority (49.5%) of the cases were in the 20-29 years age group. 73.7% were male. 82.9% of the patients were from Dang, 86% of the cases of Dang were from urban areas, and the districts bordering India accounted for 88.5% of cases. Most of the positive patients were asymptomatic (97.1%), Amongst the symptomatic cases, the most frequent clinical manifestation was both fever and cough. 8.5% of the patients also reported travel history, of which a majority had returned from India. Conclusions: The patients were mostly young males belonging to the economically active age group who were mostly affected by COVID-19 in Mid-Western Nepal. It is important to carry out age-group targeted testing to flatten the infection curve. Testing must be done irrespective of observable symptoms to overcome this public health emergency.